Global Retailers and Corporate Responsibility - Cosetta Pepe (Symphonya, 2003)
Consumers and companies are paying more attention to responsible behaviour. What is more, the percentage of consumers who state they are ready to abandon a brand for environmental reasons has grown. Companies also perceive the value of responsibility to the environment and society. Even in areas where these issues have become commonplace (primarily in the Anglo-American world), consumers tend to support the problem much more in their statements than in their actual purchasing behaviour. Where retail companies are concerned, the acceptance of responsibility to the environment and to society is reflected in a number of motivations. First of all, the possibility of distinguishing themselves from the competition, which is the element most perceived by both mainstream and specialist companies. This is true in the food sector above all and in fields where the risk of accidents is greatest. Another motivation may be the fact that they could be eligible for ethical investment funds, particularly in the USA.